Quantum polyhedra in LCAO MO theory - Carbo Dorca, R. (2016)
This paper presents the definition and characterisation of quantum molecular polyhedra. They are taken here within the description of a single molecule, using quantum molecular orbital (MO) density functions as vertices. The formalism and parameters associated to these mathematical structures are analysed. Picture Drawn by Pep Camps, Girona (2015). © 2015 Taylor & Francis